Digital Literacy: Empowering Individuals in the Digital Age - Hussain, Nazar; Phulpoto, Shumaila (CV. Bimbingan Belajar Assyfa, 2024)
This research aims to explore and measure the impact of digital literacy in empowering individuals in the digital era, focusing on various demographics, including students, working professionals, and the general public. Digital literacy is accessing, evaluating, producing, and communicating information using digital technology. Using a mixed approach, this research integrates qualitative and quantitative methods to provide a comprehensive analysis. An online survey with 500 respondents, in-depth interviews with 30 workers from various sectors, and analysis of relevant literature were carried out to collect data. The main objectives of this research are to measure the level of digital literacy in certain populations, evaluate the effectiveness of digital literacy training programs, and identify the main challenges faced in improving digital literacy, such as access to technology, basic skills, and the digital divide. Preliminary results show that digital literacy significantly improves work skills and social and economic participation. For example, individuals with higher levels of digital literacy tend to have better access to employment opportunities and are more active in online communities. This research proposes promotional strategies to increase digital literacy, including community-based training programs, formal and informal education initiatives, and government policies supporting technology access. Hopefully, this study will provide in-depth insight into how digital literacy can empower individuals and communities and offer practical solutions to overcome existing challenges. Thus, this research contributes to the academic understanding of digital literacy and provides applicable recommendations for educators, policymakers, and organizations focused on improving digital literacy.